Autophagy-mediated catabolism of visual transduction proteins prevents retinal degeneration. Issue 12 (1st December 2016) - Yao, Jingyu; Jia, Lin; Feathers, Kecia; Lin, Chengmao; Khan, Naheed W.; Klionsky, Daniel J.; Ferguson, Thomas A.; Zacks, David N.
ABSTRACT: Autophagy is a lysosomal degradation pathway critical to preventing the accumulation of cytotoxic proteins. Deletion of the essential autophagy gene Atg 5 from the rod photoreceptors of the retina ( atg5 Δ rod mouse) results in the accumulation of the phototransduction protein transducin and the degeneration of these neurons. The purpose of this study is to test the hypothesis that autophagic degradation of visual transduction proteins prevents retinal degeneration. Targeted deletion of both Gnat1 (a gene encoding the α subunit of the heterotrimeric G-protein transducin) and Atg5 in the rod photoreceptors resulted in a significantly decreased rate of rod cell degeneration as compared to the atg5 Δ rod mouse retina, and considerable preservation of photoreceptors. Supporting this we used a novel technique to immunoprecipitate green fluorescent protein (GFP)-tagged autophagosomes from the retinas of the GFP-LC3 mice and demonstrated that the visual transduction proteins transducin and ARR/arrestin are associated with autophagosome-specific proteins. Altogether, this study shows that degradation of phototransduction proteins by autophagy is necessary to prevent retinal degeneration. In addition, we demonstrate a simple and easily reproducible immunoisolation technique for enrichment of autophagosomes from the GFP-LC3 mouse retina, providing a novel application to the study of autophagosome contents across different organs and specific cell types in vivo.